Opening strategy eaudiobook Professional strategists and practice change, 1960 to today. - Whittington, Richard (HighBridge Audio, 2019)
Opening Strategy recounts the origins and development of Strategy as a profession from the middle of the last century to the present day. In particular, it focuses on how strategic planning superseded long-range planning, and the more recent rise of strategic management and open strategy. Together, these practices have contributed to growing inclusiveness and transparency in contemporary organizations. Informed by interviews with corporate strategists at leading companies around the world, eminent consultants at firms such as Bain, the Boston Consulting Group, and McKinsey & Co., and the internal archives of strategic innovators such as General Electric and Shell, this book provides vivid insights into the trials and tribulations of practice innovation in Strategy, and stresses the hard work of the little recognized and sometimes eccentric innovators within the profession. By building on a wide range of examples, covering both successes and failures, the book draws out general lessons for practice innovation in Strategy. Those studying the topic will be able to set standard strategy techniques in historical and social context and develop new areas for investigation, while practicing executives and consultants should gain a sense of how to innovate in Strategy-and how not to.